A comparative evaluation of the effectiveness of added auxiliary features, occlusal surface modifications, and reduction of total occlusal convergence on the resistance of full veneer metal crowns on a molar tooth with inadequate resistance form: An in vitro study - Nitu Agrawal; Rahul Kishore Chaudhari; Anjali Gaurishankar Gheware; Azeem Ul Yaqin Syed; Tabish Rashidi; Hadeer Bhutta (Wolters Kluwer Medknow Publications, 2021)
Introduction: Single crowns or fixed partial dentures retainers usually get dislodged due to inadequate resistance form. Hence, it is prudent to evaluate features of a tooth preparation, which can prevent these failures. Aim: To evaluate the effect of auxiliary features, occlusal surface modifications, and total occlusal convergence (TOC) on the resistance of a full veneer crown. Materials and Methods: An ivorine mandibular molar tooth was prepared with features of inadequate resistance form, i.e., 2.5 mm axial wall height and TOC of 20°. Seven auxiliary preparation features were subsequently added one by one to it. They were mesiodistal grooves, buccolingual and mesiodistal grooves, buccolingual grooves, mesiodistal boxes, occlusal inclined planes, 8° reduced TOC in the cervical aspect, and mesiodistal grooves added to 8° reduced TOC in the cervical aspect. Ten dies with their respective crowns were prepared for each group. Resistance testing of all the samples was performed on the INSTRON testing machine. Results: Modification of the overtapered die preparation by reducing the TOC to 8° in the cervical 1.5 mm of the axial wall and then subsequently adding mesiodistal grooves to the reduced TOC cervically offered the greatest resistance to dislodgment statistically. Conclusion: For an overtapered preparation, reducing the TOC to 8° in the cervical aspect and subsequently adding proximal grooves can provide maximum resistance form.